2020
DOI: 10.11604/pamj.2020.36.109.24034
|View full text |Cite
|
Sign up to set email alerts
|

Unusual sites of hydatid disease: report of two cases of dumbbell formations

Abstract: Hydatidosis is a zoonosis caused by Echinococcus granulosus . Humans are accidentally contaminated by ingesting the parasite´s eggs mainly released through the faeces from infected dogs. Hydatidosis affects the bone in 0.5 to 2% of cases, with 44% of these cases involving in the spine. Vertebral hydatidosis is rare and it represents the most frequent and most dangerous form of bone involvement. This manifestation is extremely delicate, difficult to correctly identify and manage. The auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…On review of literature we found only three such cases of dumbbell formation in which intraspinal hydatid cyst has an extension into paravertebral region through neural foramina. 11,12 Clinical symptoms may range from asymptomatic presentation to features due to pressure on surrounding structures depending on the anatomic location and size of the cysts.…”
Section: Discussionmentioning
confidence: 99%
“…On review of literature we found only three such cases of dumbbell formation in which intraspinal hydatid cyst has an extension into paravertebral region through neural foramina. 11,12 Clinical symptoms may range from asymptomatic presentation to features due to pressure on surrounding structures depending on the anatomic location and size of the cysts.…”
Section: Discussionmentioning
confidence: 99%
“… 37 A distinct type of Echinococcus granulosus infection is the dumbbell formation in which the cyst begins to form in the spinal cord and follows the neural exit foramen, forming a paravertebral extension. 38 , 39 The dumbbell type is commonly a type 4 affecting the vertebral bodies, and only rarely a type 3 or 5 manifesting without bony involvement. 40 …”
Section: Epidemiology and Classificationmentioning
confidence: 99%
“…Besides the aforementioned anatomical classification, spinal echinococcosis can also be classified according to the route of the spinal infection into primary and secondary, haematogenous and extension per continuitatem; primary haematogenous spinal echinococcosis (hematogenous infection of spinal structures at primary infection), secondary haematogenous spinal echinococcosis (haematogenous infection of spinal structures following spontaneous or iatrogenic seeding from extraspinal cystic echinococcosis), secondary extension per continuitatem spinal echinococcosis (direct invasion of spinal structures from extraspinal echinococcosis such as mediastinal and paravertebral soft tissue, pleura, lung, ribs, pelvis, posterior paravertebral muscles), and secondary extension per continuitatem spinal echinococcosis (cerebral disease with spontaneous or iatrogenic seeding into the cerebrospinal fluid, leading to intradural spinal seeding). 37 , 38 , 41 …”
Section: Epidemiology and Classificationmentioning
confidence: 99%
“…In skeletal echinococcosis, one of the most common type is spinal hydatid disease (0.2 -1%), and the thoracic spine is the top affected level (almost 50%), followed by the lumbosacral region (almost 29%) and lumbar spine (almost 21%) (Sioutis et al, 2021b;Song et al, 2007;Zlitni et al, 2001). Primary spinal hydatid disease is rare, and only four cases of primary intramedullary hydatid cysts have been reported in the literature (Dkhissi et al, 2020;Lotfinia et al, 2013). Most of patients with spinal hydatid disease have a history of extra-spine echinococcosis, and some of them are also treated by surgery (Sioutis et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%